Transmyometrial versus very difficult transcervical embryo transfer: efficacy and safety. Issue 5 (May 2016) - Khairy, Mohammed; Shah, Hany; Rajkhowa, Madhurima
Abstract: A difficult and traumatic embryo transfer can negatively impact on embryo implantation. This study retrospectively compared the outcomes of "very difficult transcervical embryo transfer" (vdTCET) versus transmyometrial embryo transfer (TMET) in a single centre over 10 years, reporting on 128 patients with vdTCET and 46 patients with TMET. The definition of vdTCET was a procedure rated by an experienced practitioner (with more than 100 transfers per year for >2 years) as very difficult and required two or more of the following: use of tenaculum, change of embryo transfer catheter and use of a stylet, reloading of the embryos or cancelling the procedure and freezing the embryo to transfer after cervical dilatation. The clinical pregnancy rates for TMET and vdTCET were 32.6% and 25%, respectively and the live birth rates were 26.1% and 16.4%, respectively. There was only one case of minor bleeding in the TMET group (2.2%). This study showed that TMET is a good alternative option in cases of vdTCET where it is impossible to achieve transcervical embryo transfer and may benefit cases with repeated failed cycles after vdTCET. Its superiority over vdTCET however could not be demonstrated.